PHOSPHORUS FERTILIZATION IN THE CROP SOYBEAN RONDONIA STATE - VALADÃO JÚNIOR, Daniel Dias; BERGAMIN, Anderson Cristian; VENTUROSO, Luciano dos Reis; SCHLINDWEIN, Jairo André; CARON, Bráulio Otomar; SCHMIDT, Denise (Scientia Agraria, 2008)
The soybean response to phosphorus (P) application in soils with P content below the critical level is inversely proportional to the available P of the soil. The objective of this paper was evaluate some response parameters of soybean cultivated in soil with low content of phosphorus, submitted at different rates of phosphorus fertilization. The experiment was located in Rolim of Moura, Rondônia state, in a Oxisol. BRS Jiripoca and BRSMT Uirapuru soybean cultivars received six rates of phosphorus fertilizer, 0, 36, 72, 110, 144 and 177 kg ha-1 of P2O5. The experiment was in a completely randomized design with three replications, and the treatments arranged in factorial 6 x 2. It was evaluated the height of plants, the height of first pod insertion and the grain yield. There is no difference between cultivars of soybean BRSMT Uirapuru and BRS Jiripoca to the answer of quantities of phosphorus in the height of plants. The quantities of phosphorus do not interfere on the height of first pod insertion. There are positives answers in grain yield due to increase the quantities of phosphorus in poor soils of this nutrient.